Qualitative and Quantitative Coronary Angiography in patients with Acute Coronary Syndrome (ACS) - Ahmed H.H. El-Adawey; Gamal F. Gomaa; Essam M. Mahfouz (Egyptian Journal of Chest Disease and Tuberculosis, 2012)
Background and Aim: Acute Coronary Syndrome (ACS) encompasses several diseases, previously thought to be separate and defined disease states. In this syndrome, Unstable Angina (UA), Non-ST Elevation Myocardial Infarction (NSTEMI), and ST-Elevation Myocardial Infarctions (STEMI) are all part of this category. The pathogenesis begins with plaque rupture which activates the platelets and coagulation cascade leading to thrombus formation. The thrombus leads to partial or complete coronary artery occlusion leading to various clinical manifestations of ACS. The aim of the present study is to assess the extent of coronary artery disease and characterizes plaque morphology and lesion severity in patients with ACS in comparison with patients with chronic stable ischemic heart disease. Subjects and Methods: To achieve this aim, we studied 100 patients with symptomatic coronary artery disease admitted to Mansoura medical Hospital, where they were subjected to full clinical evaluation; 12 lead electrocardiogram, full laboratory investigations and Coronary angiography was done to every patient, then we analyses the results both qualitative (eye ball description of angiographic lesions) and quantitative (computer-based). Those patients were classified into two main groups, the first group of patients were those with ACS (50 patients) as a test group while the second one included patients chronic stable ischemic heart disease (50 patients) as a control group. Results: Both groups were comparable and no significant difference was present as regard age, sex, diabetes mellitus, hypertension, smoking, left ventricular function, prior PTCA, prior CHF and angina class while, prior MI more frequent among test group. One hundred, forty-seven lesions (66 in test group and 81 in control group) were available for detailed qualitative angiographic analysis. Out of seven criteria analyzed only presence of lumen irregularity and thrombus were more frequent among patient who presented with ACS (17 (26%) vs. 2 (2.5%) p < 0.05; 9 (13.6%) vs. 0 (0%) p < 0.05) respectively), and this represents the main finding in the current study. No significant difference was present in Quantitative Coronary angiographic characteristics in both groups. Conclusion: The qualitative angiographic assessment represents an essential tool in the evaluation and risk stratification of patients with ACS, through the demonstration of the presence of thrombus and lumen irregularity that correlated more with ACS than the other studded criteria. In addition, QCA although added accurate assessment of the degree of luminal narrowing, thus helping in assessment of the severity of the disease.